Efficient and Precise CRISPR/Cas9-Mediated MECP2 Modifications in Human-Induced Pluripotent Stem Cells - Le, Thi Thanh Huong; Tran, Ngoc Tung; Dao, Thi Mai Lan; Nguyen, Dinh Dung; Do, Huy Duong; Ha, Thi Lien; Kühn, Ralf; Nguyen, Thanh Liem; Rajewsky, Klaus; Chu, Van Trung (Frontiers in Genetics, 2019)
Patients with Rett syndrome (RTT) have severe mental and physical disabilities. The majority of RTT patients carry a heterozygous mutation in methyl-CpG binding protein 2 (MECP2), a X-linked gene encoding an epigenetic factor crucial for normal nerve cell function. No curative therapy for RTT syndrome exists and cellular mechanisms are incompletely understood. Here, we developed a CRISPR/Cas9-mediated system that targets and corrects the disease relevant regions of the MECP2 exon 4 coding sequence. We achieved homologous recombination (HR) efficiencies of 20-30% in human cell lines and iPSCs. Furthermore, we successfully introduced a MECP2R270X mutation into the MECP2 gene in human iPSCs. Consequently, using CRISPR/Cas9 we were able to repair such mutations with high efficiency in human mutant iPSCs. In summary, we provide a new strategy for MECP2 gene targeting that can be potentially translated into gene therapy or for iPSCs-based disease modeling of RTT syndrome.